2019
DOI: 10.1177/016146811912100606
|View full text |Cite
|
Sign up to set email alerts
|

Structuring Disruption within University-Based Teacher Education Programs1: Possibilities and Challenges of Race-Based Caucuses

Abstract: Background Teacher education candidates are in different places in terms of developing their identities and relationships to equity and social justice. Various approaches have been taken within university-based teacher education programs to engage with candidates, wherever they are in this development. One such approach has been engaging or drawing on teachers’ own lenses, especially through challenging and understanding their racialized selves. Purpose This conceptual article examines how race-based caucuses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Race-based caucuses, having originated in the field of mental health, are designed as spaces for healing. Varghese et al (2019) applied the concept of race-based caucuses as an opportunity to engage in intrapersonal work collectively, showing that race-based caucuses in teacher education can facilitate much-needed intrapersonal work. Race-based caucuses create conditions in which those of shared racial identities and affinities can understand their own complicity in enacting different types of microaggression-microassaults, microinsults, and/or microinvalidations-toward themselves and others.…”
Section: Intrapersonalmentioning
confidence: 99%
See 1 more Smart Citation
“…Race-based caucuses, having originated in the field of mental health, are designed as spaces for healing. Varghese et al (2019) applied the concept of race-based caucuses as an opportunity to engage in intrapersonal work collectively, showing that race-based caucuses in teacher education can facilitate much-needed intrapersonal work. Race-based caucuses create conditions in which those of shared racial identities and affinities can understand their own complicity in enacting different types of microaggression-microassaults, microinsults, and/or microinvalidations-toward themselves and others.…”
Section: Intrapersonalmentioning
confidence: 99%
“…For example, Varghese and colleagues describe white pre‐service teachers exploring their own whiteness intrapersonally, considering consequences of their whiteness to their future teaching and characteristics of the classrooms and communities they wanted to cultivate with students. As typifies intrapersonal processes, emotional labor is at the core of race‐based caucuses, entangled with self‐reflection and self‐awareness (Varghese et al, 2019).…”
Section: Toward a Pedagogy Of Communicative Belongingmentioning
confidence: 99%
“…This reflexive analytic process requires teacher educators to also contend with the emotional geographies of exclusion of which they are a part and can help teacher educators in identifying how they might disrupt such emotional processes in their everyday interactions. Through race-based caucusing in teacher education contexts (Varghese et al, 2019), researchers and TCs can examine how they have been racialized in relation to ability in and through schools. Interrogating how whiteness and ability as property have been wielded historically and contemporarily (Annamma et al, 2013), researchers and TCs might explicitly connect these harmful realities to their own emotional relationships with ability.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…There have been ample studies using autobiographies and autoethnographies for teachers’ reaffirmation of identities (Canagarajah, 2020; Park, 2013; Varghese, Daniels, & Park, 2019; Yazan, 2019; Yazan, Canagarajah, & Jain, 2020; Yazan & Lindahl, 2020). Among them, Yazan (2019) explored using autoethnography to investigate language ideologies and identity positions and found that ideological binaries had been destabilized as the participant constructed her teacher identity through narrative (p. 1).…”
Section: Literature Reviewmentioning
confidence: 99%